Health literacy and information needs among German skin cancer patients in comparison to people without skin cancer: A survey - Hoffmann, Julia; Steeb, Theresa; Weber, Christiane; Doppler, Astrid; Schmitt, Jochen; Schadendorf, Dirk; Berking, Carola; Meier, Friedegund (JEADV Clinical Practice, 2023)
Background: An increasing number of patients are seeking health information on the internet. Health literacy and the quality of information are crucial to enable patients to find relevant high-quality information. Objectives: To investigate the relevance of quality criteria for health information and to determine the health literacy of skin cancer patients (SC) in comparison to those without skin cancer (NSC). Methods: Between December 2021 until February 2022 we undertook an online survey on the importance of multiple criteria to investigate the relevance of quality criteria of online health information. SC and NSC were eligible for participation. The questionnaire assessed participants´ health information-seeking behavior and the evaluation of relevance of quality criteria for health information on a 5-point-LIKERT-Scale. The participants´ health literacy was measured according to the health literacy measurement scale ranging from 0-100. Comparisons between SC and NSC were investigated with t-tests. Results: We retrieved data from 268 participants, of whom 98 (38%) were SC. Participants assigned the highest relevance to the health information topics treatment (4.7 ± 0.64) and effects of a disease (4.49 ± 0.76). Participants ranked the content of information with a mean of 4.72 (±0.57) to be the most relevant criterion, followed by objectivity (4.61 ± 0.67) and completeness of the information (4.59 ± 0.61). Participants showed the highest competence in understanding of information (62.4 ± 22.5) and in disease prevention (58.32 ± 22.9). They reached low values in accessing health related information (46.78 ± 25.62) and appraising it (33.16 ± 20.11). Subgroup analysis indicated that SC had a greater need for practical information that is helpful in dealing with a disease compared to NSC. They showed significantly lower health literacy than NSC. Conclusions: Our study documents that SC and NSC have a high need for different dimensions of quality of health information. These differences in the importance of criteria should be considered in the development of future targeted health information.
CRIS-Team Scopus Importer:2024-12-16
Keywords: health communication; health information; health literacy; quality criteria; skin cancer; survey